1995
DOI: 10.1111/j.1365-2125.1995.tb04481.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypertension in the elderly: attitudes of general practitioners and hospital physicians.

Abstract: 1 The attitudes of general practitioners and hospital physicians to the management of hypertension in the elderly, were examined by responses to a postal questionnaire distributed within the Northern Region, concerning the management of a healthy 75 year old male non-smoker with sustained diastolic or isolated systolic hypertension. 2 Two hundred and fourteen (64%) general practitioners and 127 (70%) hospital physicians responded to the questionnaire. General practitioners stated they would most commonly measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…We have established that thaizide diuretics is the most frequently prescribed agent either as a monotherapy or combination therapy for the management of hypertension in our study site. This finding was similar to the results of the studies from Britain, Italy, Spain, South Africa and Canada where diuretics have been shown to be the most popular medication for the treatment of hypertension (Ford and Asghar, 1995;Wallenius et al, 1988;Edward et al, 1998). This practice is in line with the JNC 7 report which have placed emphasize on the use of thaizide type diuretics as first line agent for the management of hypertension.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have established that thaizide diuretics is the most frequently prescribed agent either as a monotherapy or combination therapy for the management of hypertension in our study site. This finding was similar to the results of the studies from Britain, Italy, Spain, South Africa and Canada where diuretics have been shown to be the most popular medication for the treatment of hypertension (Ford and Asghar, 1995;Wallenius et al, 1988;Edward et al, 1998). This practice is in line with the JNC 7 report which have placed emphasize on the use of thaizide type diuretics as first line agent for the management of hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…The 2014 evidence-based guidelines for the management of high blood pressure in adults (JNC 8) also favoured the use of thiazide diuretics and CCBs as initial therapies in blacks (James et al, 2014). In countries like Taiwan and the United States, CCB were the most prescribed medication for the management of hypertension (Ford and Asghar, 1995;Chou et al, 2004). Meanwhile, many studies support the use of CCB and diuretics in the elderly and black Africans (ALLHAT Collaborative Research Group, 2002;Adigun et al, 2003) in line with the newly published guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is still a demand for more easily tolerated medications that may improve patient compliance and the control of hypertension. 29,30 Even if pharmaceutical therapy is optimized to modify risk factors for stroke, the most effective means of reducing stroke risk are those incorporating lifestyle changes. When feasible, this should be the first approach taken with patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 2002/2003 WHO‐ISH and European guidelines suggested that ACEIs, ARBs, BBs, CCBs, and thiazides are all drugs of first choice. It was also noted in Britain, Italy, Spain, South Africa, and Canada that diuretics were a popular treatment for hypertension 56 – 58 . Reports on the influence of practice guidelines on physician behavior indicate that there is suboptimal adherence to guidelines 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted in Britain, Italy, Spain, South Africa, and Canada that diuretics were a popular treatment for hypertension. [56][57][58] Reports on the influence of practice guidelines on physician behavior indicate that there is suboptimal adherence to guidelines. 59 Other research has shown little effect of clinical trials on prescribing patterns.…”
Section: Figure 2 Prescribing Trends For Patients With and Without Dmentioning
confidence: 99%